2022
DOI: 10.1111/jam.15732
|View full text |Cite
|
Sign up to set email alerts
|

AaCaM is required for infection structure differentiation and secondary metabolites in pear fungal pathogen Alternaria alternata

Abstract: Aims Calmodulin (CaM), acts as a kind of multifunctional Ca2+ sensing protein, which is ubiquitous in fungi, is highly conserved across eukaryotes and is involved in the regulation of a range of physiological processes, including morphogenesis, reproduction and secondary metabolites biosynthesis. Our aim was to understand the characteristics and functions of AaCaM in Alternaria alternata, the causal agent of pear black spot. Methods and results A 450 bp cDNA sequence of AaCaM gene of A. alternata was cloned by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…PKCs are involved in the Ca 2+ signaling pathway and play important roles in fungal growth, development, and pathogenicity, and are potential targets of antifungal drugs [ 11 , 12 , 14 , 43 ]. PKCs comprise an important class of pathogenic factors, and studies have confirmed that they are involved in the pathogenesis of a variety of phytopathogenic fungi [ 16 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKCs are involved in the Ca 2+ signaling pathway and play important roles in fungal growth, development, and pathogenicity, and are potential targets of antifungal drugs [ 11 , 12 , 14 , 43 ]. PKCs comprise an important class of pathogenic factors, and studies have confirmed that they are involved in the pathogenesis of a variety of phytopathogenic fungi [ 16 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, previous studies have demonstrated that V. dahliae primarily thrives as stress-resistant microsclerotia in adverse environments. The formation of microsclerotia is accompanied by the accumulation of melanin, which finally transforms into mature black microsclerotia with strong stress resistance [ 30 , 33 , 43 , 61 ]. The present study revealed that VdPKC regulates the transcription of melanin and sclerotia-related genes ( Figure 5 D), thereby affecting the formation of microsclerotia and melanin.…”
Section: Discussionmentioning
confidence: 99%
“…Upon Ca 2+ presence, the activated CaM binds to the CNA and CNB complexes to form a fully activated trimer [ 81 ], and then activated CaN dephosphorylates Crz1 and transfers it to the nucleus to regulate the expression of Crz1-dependent genes [ 11 , 82 ]. In fungi, the CaN-Crz1 signaling pathway is also conserved and involved in many biological processes, such as cell growth, infection structure differentiation, cell wall integrity, pathogenicity and stress response [ 83 , 84 , 85 , 86 , 87 ] ( Figure 1 ). The Figure 1 only depicts genes in the calcium signaling pathway that are closely linked to Crz1 or directly regulated by Crz1.…”
Section: Calcium Signaling Pathway In Fungal Cellmentioning
confidence: 99%